Subscribers’ intention towards using 3G mobile services - Suki, Norazah Mohd (Journal of Economics and Behavioral Studies, 2011)
3G mobile network offers higher data rates than the previous generation networks (1G and 2G). The purpose of this study is to examine the factors influencing subscribers’ intention towards using 3G mobile services with the Technology Acceptance Model (TAM) as the guiding principle. Cross sectional data were collected through a survey and analyzed by means of factor analysis, correlation and regression analysis. Out of 150 questionnaires, only 100 were usable. Findings show that Perceived Usefulness, Perceived Ease of Use and Attitude are jointly responsible in determining the subscribers’ intention to use of 3G mobile services. Perceived Usefulness was found as a key factor influences subscribers’ intention to use 3G mobile services. In addition, implications and direction for future research are discussed.